Electrochemical Evaluation of Nickel Oxide Addition toward Lanthanum Strontium Cobalt Ferrite Cathode for Intermediate Temperature Solid Oxide Fuel Cell (IT-SOFCS) - Ahmad Fuzamy Mohd Abd Fatah; Ahmad Zaki Rosli; Ahmad Azmin Mohamad; Andanastuti Muchtar; Muhammed Ali S.A.; Noorashrina A. Hamid (Energies, 2022)
A mixture of lanthanum strontium cobalt ferrite (LSCF) and nickel oxide (NiO) makes for a desirable cathode material for an IT-SOFC due to its excellent oxygen reduction capability. This study investigates the effect of NiO addition into LSCF cathode on its physical and electrochemical properties. To optimise the amount of NiO addition, both electrochemical impedance spectra and bode phase were used to examine various weight ratios of nickel oxide and LSCF cathode. Brunauer-Emmett-Teller (BET) and thermal analyses validated the electrochemical observation that the LSCF:NiO ratio yields sensible oxygen reduction reaction and stoichiometric findings. Initial characterisation, comprising of phase and bonding analyses, indicated that LSCF-NiO was successfully synthesised at 800 °C using an improved modified sol gel technique. The addition of 5% nickel oxide to LSCF results in the lowest area specific resistance (ASR) value overall. The Bode phase implies that the addition of 5% nickel oxide to LSCF reduces the impedance at low frequencies by 64.28 percent, indicating that a greater oxygen reduction process happened at the cathode. After the addition of 5 wt% NiO, a single LSCF-NiO cell may function at temperatures as low as 650 °C and the LSCF cathode power density is increased by 25.35%. The surface morphology of the LSCF-NiO cathode reveals that the average particle size is less than 100 nm, and mapping analysis demonstrated a homogenous NiO distribution over the cathode layer. Consequently, the synthesis of LSCF-NiO at intermediate temperatures (800–600 °C) revealed outstanding chemical compatibility, bonding characteristics, and electrochemical performance.